Plantmediated horizontal transmission of Wolbachia between whiteflies - Li, Shao-Jian (ISME J, 2017)
Maternal transmission is the main transmission pathway of facultative bacterial endosymbionts, but phylogenetically distant insect hosts harbor closely related endosymbionts, suggesting that horizontal transmission occurs in nature. Here we report the first case of plant-mediated horizontal transmission of Wolbachia between infected and uninfected Bemisia tabaci AsiaII7 whiteflies. After infected whiteflies fed on cotton leaves, Wolbachia was visualized, both in the phloem vessels and in some novel ‘reservoir' spherules along the phloem by fluorescence in situ hybridization using Wolbachia-specific 16S rRNA probes and transmission electron microscopy. Wolbachia persisted in the plant leaves for at least 50 days. When the Wolbachia-free whiteflies fed on the infected plant leaves, the majority of them became infected with the symbiont and vertically transmitted it to their progeny. Multilocus sequence typing and sequencing of the wsp (Wolbachia surface protein) gene confirmed that the sequence type of Wolbachia in the donor whiteflies, cotton phloem and the recipient whiteflies are all identical (sequence type 388). These results were replicated using cowpea and cucumber plants, suggesting that horizontal transmission is also possible through other plant species. Our findings may help explain why Wolbachia bacteria are so abundant in arthropods, and suggest that in some species, Wolbachia may be maintained in populations by horizontal transmission.